Mediators of Intervention Effects on Dietary Fat Intake in Low-Income Overweight or Obese Women with Young Children - Chang, Mei-Wei (Appetite, 2020)
PURPOSE. We investigated whether autonomous motivation and self-efficacy might mediate the association between a lifestyle behavior intervention and dietary fat intake in low-income overweight or obese women with young children. METHODS. Participants were randomized to an intervention or comparison group. Intervention participants received a 16-week intervention aimed to prevent weight gain through promotion of stress management, healthy eating and physical activity. During the intervention phase, participants viewed a designated video lesson at home and dialed in a peer support group teleconference every week (weeks 1–4) then every other week (weeks 5–16). Potential mediation effects were analyzed using sequential mixed-effects linear models and path analysis. RESULTS. The intervention led to increased autonomous motivation (β = 0.34, standard error [SE] = 0.15, P = 0.005), which subsequently increased self-efficacy (β = 0.18, SE = 0.35, P < 0.001), and higher levels of self-efficacy were associated with decreased dietary fat intake (β = −0.22, SE = 0.28, P < 0.001). In other words, autonomous motivation and self-efficacy mediated the association between the lifestyle behavior intervention and dietary fat intake. CONCLUSION. To decrease dietary fat intake for low-income overweight or obese women with young children, strategies, such as those promoting peer encouragement, may be warranted in interventions to enhance autonomous motivation and/or practical skills for increasing self-efficacy.